2022
DOI: 10.1186/s40793-022-00437-x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic assembly reveals hosts and mobility of common antibiotic resistome in animal manure and commercial compost

Abstract: Background Antibiotics and antibiotic resistance genes (ARGs) used in intensive animal farming threaten human health worldwide; however, the common resistome, ARG mobility, and ARG host composition in different animal manures and mixed manure composts remain unclear. In the present study, metagenomic assembly and cross-sample mapping were used to comprehensively decipher the common resistome and its potential mobility and hosts in animal manure and composts. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…For instance, tetracycline resistance genes are ubiquitous and abundant in the human gut worldwide, , aminoglycoside and beta-lactam resistant genes have been shown to be the most abundant ARG types in urban park soil with reclaimed water irrigation, and multidrug resistance genes, vancomycin, and beta-lactam resistant genes are the most diverse and dominant ARGs in collembola. , However, ARGs conferring resistance to multidrug, beta-lactam, and MLS resistance genes were found to be dominant in the gut microbiome of the giant African snails we studied. Our study revealed that multidrug resistance accounted for 60% of the total ARG abundance in giant African snails, exceeding other environmental samples such as urban streams, livestock manure, and untreated urban sewage . This high ratio of multidrug resistance in giant African snails sets it apart from related studies and calls for further attention, especially given the increasing prevalence of multidrug-resistant pathogenic bacteria worldwide, which poses significant challenges to disease control …”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For instance, tetracycline resistance genes are ubiquitous and abundant in the human gut worldwide, , aminoglycoside and beta-lactam resistant genes have been shown to be the most abundant ARG types in urban park soil with reclaimed water irrigation, and multidrug resistance genes, vancomycin, and beta-lactam resistant genes are the most diverse and dominant ARGs in collembola. , However, ARGs conferring resistance to multidrug, beta-lactam, and MLS resistance genes were found to be dominant in the gut microbiome of the giant African snails we studied. Our study revealed that multidrug resistance accounted for 60% of the total ARG abundance in giant African snails, exceeding other environmental samples such as urban streams, livestock manure, and untreated urban sewage . This high ratio of multidrug resistance in giant African snails sets it apart from related studies and calls for further attention, especially given the increasing prevalence of multidrug-resistant pathogenic bacteria worldwide, which poses significant challenges to disease control …”
Section: Discussionmentioning
confidence: 75%
“…24,73 However, ARGs conferring resistance to multidrug, beta-lactam, and MLS resistance genes were found to be dominant in the gut microbiome of the giant African snails we studied. Our study revealed that multidrug resistance accounted for 60% of the total ARG abundance in giant African snails, exceeding other environmental samples such as urban streams, 74 livestock manure, 69 and untreated urban sewage. 75 This high ratio of multidrug resistance in giant African snails sets it apart from related studies and calls for further attention, especially given the increasing prevalence of multidrug-resistant pathogenic bacteria worldwide, which poses significant challenges to disease control.…”
Section: Effect Of Urbanization On Giant African Snailsmentioning
confidence: 68%
See 1 more Smart Citation
“…Specifically, AMX is the most commonly used human and animal antibiotic among 36 different drug types in China ( Liu et al, 2019 ), with doses up to 500 mg/kg used in pig feed ( Liu et al, 2018 ). However, antibiotics usage in animal husbandry ( Zhang et al, 2017a ) can shift animal microbiome, enrich antibiotic resistance genes (ARGs), and subsequently transfer to livestock manure and its products ( Qiu et al, 2022 ). Hence, livestock production is considered an important hotspot and key point-source of antibiotic resistant bacteria (ARB) and ARGs dissemination ( Youngquist et al, 2016 ; Awasthi et al, 2019 ; Deng et al, 2020 ; Lu et al, 2020 ; Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the soil microbiota naturally presents a large and robust diversity of ARGs in its intrinsic resistome, land use transformation due to anthropic activities, such as the excessive use of antibiotics in livestock production [4], antibiotic-enriched manure application [5,6], and excessive use of xenobiotics in crops [7,8], along with increasing levels of deforestation for farming or urban purposes, can alter bacterial communities and disseminate ARGs throughout the environment [9]. In these highly modified sites, soil bacteria more frequently are in close proximity to commensal and pathogenic ones, which could lead to an increased horizontal ARG transfer rate among them, followed by a dominance of organisms with acquired resistance in comparison to intrinsically resistant bacteria [10].…”
Section: Introductionmentioning
confidence: 99%